The comparative evaluation of carbon mineralization in soils contaminated and uncontaminated with chromium - Kızıldağ, Nacide; Sağlıker, Hüsniye Aka; Darıcı, Cengiz (Penerbit Universiti Kebangsaan Malaysia, 2017)
The environmental risk of Chromium (Cr) pollution is pronounced in soils adjacent to chromate industry. It is important to investigate the functioning of soil microorganisms in ecosystems exposed to long-term contamination by Cr. The aim of this study was to determine the effects of Cr on carbon mineralization in soil. The study was carried out in soils contaminated and uncontaminated with Cr near and away from a Cr mine in three different districts (Bozluk, Kızılyüksek and Yanıkçam) of East Mediterranean Region, Turkey. Carbon mineralization were determined in soils humidified 80% of field capacity at 28°C over 30 days under the same laboratory conditions. These results showed that carbon mineralization was greatly inhibited by the presence of Cr in all contaminated sites. Based on these results, microbial activity can use as an indicator for the Cr pollution level in the soil ecosystems.